2008
DOI: 10.1002/joc.1662
|View full text |Cite
|
Sign up to set email alerts
|

Effects of precipitation, temperature and topographic parameters on evergreen vegetation greenery in the Western Ghats, India

Abstract: Bi-weekly National Oceanic and Atmospheric Administration-advanced very high-resolution radiometer (NOAA-AVHRR) satellite data covering a fourteen-year time period (1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003) were used to examine spatial patterns in the normalized difference vegetation index (NDVI) and their relationships with environmental variables covering tropical evergreen forests of the Western Ghats, India. NDVI values and corresponding environmental variables wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 65 publications
1
23
0
Order By: Relevance
“…[9] reports that the vegetation over India is decreasing during drought years while opposite results are shown during flood years. There are many studies done over Indian subcontinent on vegetation variability and its relation to meteorological parameters [5,12]. In order to understand the association of NDVI with rain fall over Bangladesh interannual variations, spatial correlation, scatter plot and annual correlation analysis are observed.…”
Section: B Association Of Ndvi With Rainfallmentioning
confidence: 99%
“…[9] reports that the vegetation over India is decreasing during drought years while opposite results are shown during flood years. There are many studies done over Indian subcontinent on vegetation variability and its relation to meteorological parameters [5,12]. In order to understand the association of NDVI with rain fall over Bangladesh interannual variations, spatial correlation, scatter plot and annual correlation analysis are observed.…”
Section: B Association Of Ndvi With Rainfallmentioning
confidence: 99%
“…Average, minimum, and maximum temperatures were important driving factors in the evergreen forest dynamic, having positive effects. Similarly, Prasad et al [2] concluded that the Continental Index-the difference between minimum and maximum temperature-demonstrated a higher influence on the evergreen forest compared with the combined precipitation parameters and topographic parameters. Moreover, Guo et al [19] suggested that the rising temperature may increase forest growth at the beginning of the growing period, but precipitation may decrease NDVI in the forest biome.…”
Section: Climate Driving Factors Of Vegetation Dynamicsmentioning
confidence: 96%
“…were used to identify the driving climatic factors and their effects on vegetation dynamics [2,3]. The conclusions are illustrated in Table 3.…”
Section: Climate Driving Factors Of Vegetation Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also reported that due to climate change, the Western Ghats is going to receive exceptional amounts of rainfall during south west monsoon season which brings high contrast in the plant richness and diversity. Prasad et al (2008) studied the effects of precipitation, temperature and topographic parameters on evergreen vegetation greenery in the Western Ghats, India and reported that the vegetion in Western Ghats is strongly dependant on seasonal rainfall. However, a few reports only available on the relationship of NDVI and rainfall and other climatic indices.…”
Section: Introductionmentioning
confidence: 99%